Overview The Implementation Of Discharge Planning By Nurse In Hospital: Literature Review - Eva Supriatin; Nursiva Indrawati; Linlin Lindayani; Diwa Agus Sudrajat (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2021)
Background: Discharge planning is the process of interaction among of nurse, patient and family to manage the continuation treatment which is needed by the patient during the transition from hospital to home. Whatever the result is from discharge planning will have an impact on the quality of nursing treatment and the quality of patient health. Objective: Describing the implementation of nurse discharge planning in a hospital based on previous research. Methods: The type of this research is literature review. The quality in each journal is assessed using the JBI critical appraisal tools assessment to review selected articles. Results: Four of the seven journals which are selected, describe the discharge planning of nurse in the favorable category and three others describe in the unfavorable category. Conclusion: The good categorized nurse discharge discharge consists of five stages beginning in the examination stage, nursing diagnosis, planning, implementation, and evaluation stage. It is hoped that the results of this literature review can provide education and information for scientology, institutions, hospitals associated with customs duties. Recommendations: Nurses and medical teams are advised to facilitate the transition of patients from hospital to home especially with education related to increased knowledge of the patient and the family.